2023
DOI: 10.1002/lsm.23672
|View full text |Cite
|
Sign up to set email alerts
|

Light and energy‐based therapeutics for genitourinary applications: Consensus on protocols and best practices

Abstract: Background: Lasers and energy-based technologies have been developed for genitourinary applications over the past several decades. Aims: This consensus article aims to categorize the published articles and clinical trial data that culminated in protocol development of technology for genitourinary applications, and to develop consistent parameters in future clinical trials. Materials and Methods: The published articles and clinical trials data on lasers and energy-based devices applied to genitourinary conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Table 2 includes currently available fractionated laser options and dates of clearance for use by the FDA through the 510k process, meaning that the lasers were cleared on the basis of similar prior predicate devices. 25…”
Section: Modern Fractionated Lasersmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 includes currently available fractionated laser options and dates of clearance for use by the FDA through the 510k process, meaning that the lasers were cleared on the basis of similar prior predicate devices. 25…”
Section: Modern Fractionated Lasersmentioning
confidence: 99%
“…Many studies have demonstrated feasibility, tolerability, and positive effects of vaginal laser on genitourinary conditions; however, data quality has been deemed low and very low, and higher-quality clinical trials are needed to change current clinical practice recommendations. A recent consensus article by Alexiades et al 25 reviewed clinical trial data for lasers on genitourinary conditions and aimed to develop protocols and practices for the use of laser in future clinical trials, which may allow comparable data and meta-analyses. The consensus document lists common brands of CO 2 and Er:YAG laser devices and their manufacturer-recommended settings and describes a treatment schedule of three treatments at 1-month intervals, with a maintenance treatment between 6 and 12 months of follow-up.…”
Section: Genitourinary Syndrome Of Menopausementioning
confidence: 99%
See 1 more Smart Citation